microRNAs and Gene–Environment Interactions in Autism: Effects of Prenatal Maternal Stress and the SERT Gene on Maternal microRNA Expression - Beversdorf, David Q.; Shah, Ayten; Jhin, Allison; Noel-MacDonnell, Janelle; Hecht, Patrick; Ferguson, Bradley J.; Bruce, Danielle; Tilley, Michael; Talebizadeh, Zohreh (Frontiers in Psychiatry, 2021)
Background: Genetics and environment both are critical in autism spectrum disorder (ASD), but their interaction is less understood. Numerous studies have shown higher incidence of stress exposures during pregnancies with children later diagnosed with ASD. However, many stress-exposed mothers have unaffected children. The serotonin transporter (SERT) gene affects stress reactivity. Two independent samples have shown that the association between maternal stress exposure and ASD is greatest with maternal presence of the SERT short (S)-allele (deletion in the promoter region). microRNAs play a regulatory role in the serotonergic pathway and in prenatal stress, and are therefore potential mechanistic targets in this setting. Design/Methods: We profiled microRNA expression in blood from mothers of children with ASD, with known stress exposure during pregnancy. Samples were divided into groups based on SERT genotypes (LL/LS/SS) and prenatal stress level (high/low). Results: 2500 mature microRNAs were examined. ANOVA showed differential expression (DE) of 119 microRNAs, 90 were DE in high- vs low-stress groups (stress-dependent). Two (miR-1224-5p, miR-331-3p) were recently reported to exhibit stress-dependent expression in rodent brain samples from embryos exposed to prenatal stress. Another, miR-145-5p, is associated with maternal stress. Across SERT genotypes, with high stress exposure, 20 significantly DE microRNAs were detected, five were stress-dependent. These microRNAs may be candidates for stress X SERT genotype interactions. This is remarkable as these changes were from mothers several years after stress-exposed pregnancies. Conclusions: Our study provides evidence for epigenetic alterations in relation to a G x E model (prenatal maternal stress X SERT gene) in ASD.